Systematic minireview of the craniocervical junction in dogs with and without brachycephaly - Wess, Lukas; Kneissl, Sibylle (Frontiers in Veterinary Science, 2024)
Objective: To identify, quantify and compare clinical and concurrent imaging findings of occipital hypoplasia (OH), syringomyelia (SM) and atlanto-occipital overlapping (AO) in dogs with or without brachycephaly.A focused systematic search for literature was performed in the Web of Science™, PubMed and Google Scholar databases. Both authors screened and classified the identified articles using EndNote and appraised the articles using the Critical Appraisal Skills Program checklists. The main clinical and concurrent imaging features were extracted and evaluated for coexistence of OH, SM, AO, and other imaging findings.Results: Thirty-one articles were included in this minireview. For articles focusing on descriptions of OH, SM and AO, 249 dogs had at least one of these conditions, and 3 of these 249 dogs (1%) had coexistence of all three conditions. For articles focusing on descriptions of the dogs, OH, SM, and AO were identified in 552/19/11/11, 574/2/0/6, and 100/0/0/0 small brachycephalic, small nonbrachycephalic, large brachycephalic, and large non-brachycephalic breeds, respectively. For all . small brachycephalic dogs, the percentages of affected animals were 40% for OH (p=0.01), 42% for SM (p<0.01) and 7% for AO (p=0.033). The number of dogs having AO and clinical symptoms is low (n=5).Conclusions: OH, SM and AO are more likely to affect small dogs. AO might be limited to small brachycephalic breeds owing to the geometry of the craniocervical junction. Hence, AO alone might not lead to SM. In individual dogs, readers should carefully interpret the clinical relevance of OH or AO in the absence of SM.